Nur Bun cultivation and soil health An indigenous way of farming in hilly ecosystem of Meghalaya - Savita, Savita; Choudhury, B U; Krishnappa, R (Indian Farming, 2019)
Meghalaya being a hilly and mountainous state with fragile and sloppy ecosystem, is considered asthe most rain soaked region of India and the globe. Majority of inhabitants of the state belongingto different tribes rely primarily on agriculture for their livelihood (ca. 83%). The ethniccommunities of state mostly follow two types of primitive agricultural practices viz., shiftingcultivation and bun cultivation. Shifting cultivation (jhum) or slash/burn agriculture ispracticed majorly in and around forests, is one of the most ancient systems of farming, believed tohave originated in the Neolithic period around 7000 BC. This primitive form of cultivationpractice is a transition between food gathering and hunting, to intense food production. Moreover,some of tree based farming practices are also prevalent among interior parts of the state. Buncultivation is a modified system of the jhum cultivation which is practiced across the northeaststates.